Defossilization: A Review of 3D Printing in Experimental Paleontology - Johnson, Erynn H.; Carter, Aja M. (Frontiers in Ecology and Evolution, 2019)
3D printing has made it possible to recreate, actuate, and modify replicas of ancient life in transformative ways— revolutionizing studies of ancient life. While 3D printing has previously been emphasized as an educational tool in paleontology, it has also created a wide array of experimental opportunities previously unavailable to investigators. Although 3D printing has been used extensively for experimental studies in many STEM fields, the biases of the fossil record and constraints of the fossilization process create unique challenges for paleontological studies. Here, we outline a guide for using this technology for experimental paleontology: from designing a virtual model to choosing the most effective printing material—highlighting successful employment of these methods by previous investigators. As it can be challenging to adopt new methods in a meaningful way, we hope that this paper will serve as a useful tool for current and future paleontologists who seek to apply these techniques.